Synthesis of temperature and pH/CO2 responsive homopolymer bearing oligo(ethylene glycol) unit and N, N-diethylamino ethyl group and its solution property. (1st May 2015) - Jiang, Xue; Feng, Chun; Lu, Guolin; Huang, Xiaoyu
Abstract: A homopolymer strategy was developed to synthesize temperature and pH/CO2 stimulus-responsive homopolymers. A new class of acrylamide monomers bearing oligo(ethylene glycol) unit and N, N -diethylaminoethyl group were designed and prepared through Aza-Michael addition reaction followed by amidation with acryloyl chloride using amino group as a linkage to connect oligo(ethylene glycol), N, N -diethylaminoethyl, and polymerizable double bond groups together. Subsequently, the corresponding homopolymers containing oligo(ethylene glycol) unit and N, N -diethylaminoethyl group in each repeated unit were prepared via RAFT polymerization with controlled molecular weights and relatively narrow molecular weight distributions. The lower critical solution temperature (LCST) of homopolymer was examined to be influenced by molecular weight, salt concentration, and pH value of aqueous solution. The LCSTs of homopolymers could be tuned in a wide temperature window by changing pH value of aqueous solution and it increased with the decrease of pH value. Particularly, CO2 gas as a unique pH stimulus can also reversibly adjust the solubility of homopolymer without the addition of acids or bases. Graphical abstract: Highlights: A new class of acrylamide monomer was prepared through Aza-Michael reaction. Homopolymers with OEG and DEAE groups were prepared via RAFT. LCSTs of homopolymer could be tuned by changing pH value. CO2 gas can reversibly adjust the solubility of homopolymer.